Comparative analysis of variables causing happiness in Turkish youth employment - Korkmaz, Murat; Yücel, Ali Serdar; Şahbudak, Ercan; Germir, Hatice Nur; Şen, Erdal; Karta, Nurullah (My University, 2015)
In this study, it was aimed to examine practically the relationship of variables with each other which cause personal happiness by using 2007-2013 data of Turkish Statistical Institute (TSI). Data acquired from this study was analyzed with E-Views 8.0 program. As a result of regression and correlation analyses, factors affecting workforce at the most were determined. At the end of the study, it was tried to determine positive and negative relationships among hope rate, happiness rate, love, success, business, trip, entertainment, sports and cultural activities, relative and friend visits and business trips (conference, meeting, duty, etc.) which cause happiness in youth employment.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Employment; Happiness; Variable; Young; TSI; Relationship